Geochemical and radioactivity characterization of rocks from the Rio Preto (Go) Project - Duarte, Cynthia Romariz; Bonotto, Daniel Marcos [UNESP]; de Oliveira, Marcos Aurélio Farias [UNESP] (My University, 2013)
The Rio Preto Project, developed by the extinct Brazilian nuclear state company, Nuclebrás, during the late 70s and early 80s, consisted of basic geological mapping and radiometric characterization by aerogeophysical gamma-ray spectrometry, without channel discrimination, of a surface area of 650 km2 located to the west of the Chapada dos Veadeiros National Park on the northeastern of Goiás State, Brazil, including the confluence area of Claro and Preto Rivers. Additionally, the natural radioelements U, Th and 40K were determined by gamma-ray spectrometry in 300 rock samples from cores of the Rio Preto Project area. The tests were conducted at LABIDRO-Isotopes and Hydrochemistry Laboratory of the Departament of Petrology and Metallogeny (DPM) of the Institute of Geosciences and Exact Sciences, UNESP, in Rio Claro, SP, Brazil. This paper reports the results of petrographic characterization and chemical analyses of major oxides (SiO2, TiO2, Al2O3, Fe2O3, MgO, MnO, K2O, Na2O, CaO and P2O5) for all samples used to determine the natural radioelements present in the region. The organic matter content results obtained by colorimetry are also reported for selected cores of different lithotypes in order to investigate the possible relationship between graphite and the radioelements uranium and thorium. Finally, uranium content and 234U/238U activity ratio data for selected samples of schists and gneisses of the Lower Member of the Ticunzal Formation suggest the influence of weathering processes in the area. © 2012 Sociedade Brasileira de Geofísica.
Keywords: Gamma and alpha spectrometry; Natural radioelements; Rio Preto (GO) Project; gamma ray radiation; geochemical method; graphite; hydrochemistry; organic matter; oxide; radioactive pollution; radioactivity; radiometer; river pollution; spectrometry; thorium; uranium; Brazil; Minas Gerais; Rio Preto State Park